2013
DOI: 10.1016/j.clim.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the roles of STAT5B and STAT5A in human CD4+ T cells

Abstract: STAT5A and STAT5B are highly homologous proteins whose distinctive roles in human immunity remain unclear. However, STAT5A sufficiency cannot compensate for STAT5B defects, and human STAT5B deficiency, a rare autosomal recessive primary immunodeficiency, is characterized by chronic lung disease, growth failure and autoimmunity associated with regulatory T cell (Treg) reduction. We therefore hypothesized that STAT5A and STAT5B play unique roles in CD4+ T cells. Upon knocking down STAT5A or STAT5B in human prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
0
32
2
1
Order By: Relevance
“…[18][19][20] These phenotypes are consistent with major non-redundant roles for STAT5B in regulation of target genes such as FoxP3 and IGF1. Knockdown studies of STAT5A and STAT5B in human CD4 + T cells confirmed this specificity for FoxP3 21 and knockdown studies in IL-3 stimulated murine BaF3 cells identified overlapping and unique sets of STAT5 target genes by chromatin immunoprecipitation. 22 Interestingly, the ability for STAT5 binding to modulate gene expression appears to be under additional levels of regulation such as serine phosphorylation [23][24][25] and glycosylation 26 which may influence interactions with CREB-binding protein.…”
Section: Stat5 Activation In Hematopoietic Stem and Progenitor Cellsmentioning
confidence: 87%
“…[18][19][20] These phenotypes are consistent with major non-redundant roles for STAT5B in regulation of target genes such as FoxP3 and IGF1. Knockdown studies of STAT5A and STAT5B in human CD4 + T cells confirmed this specificity for FoxP3 21 and knockdown studies in IL-3 stimulated murine BaF3 cells identified overlapping and unique sets of STAT5 target genes by chromatin immunoprecipitation. 22 Interestingly, the ability for STAT5 binding to modulate gene expression appears to be under additional levels of regulation such as serine phosphorylation [23][24][25] and glycosylation 26 which may influence interactions with CREB-binding protein.…”
Section: Stat5 Activation In Hematopoietic Stem and Progenitor Cellsmentioning
confidence: 87%
“…The increased susceptibility to opportunistic infections could also be related to decreased CD25 on all T cells, as has been reported in humans with severe CD25 deficiency (50). The forkhead-box family of transcription factor, FOXP3, shown to be regulated by STAT5 (51,52), is highly expressed in Treg, but was significantly reduced in STAT5B deficient Treg (48,53). Altogether, the reduced CD25 high and FOXP3 expression associated with homozygous STAT5B mutations appears likely to have contributed to the novel immunodeficiency observed in these patients.…”
Section: Impact Of Stat5b Deficiency On Immunitymentioning
confidence: 99%
“…There is also evidence for STAT5 involvement, as RNAi of STAT5B in human CD4 + T cells results in decreased Treg cell numbers upon stimulation under Treg skewing conditions, and diminished suppressive function [44]. These findings suggest interactions and coordinated actions between STAT and mTOR pathways in Treg differentiation, and potentially function and maintenance in the periphery.…”
Section: Coordinated Functions Of Mtor and Stat Pathways In T Cellsmentioning
confidence: 99%